(untitled) (Praxis Educativa, 2012)
Past decades have seen a notable expansion of enrollment in higher education in our country; meanwhile, it took place an increase in the number of students entering universities with non traditional academic backgrounds, after a variable number of years from the completion of high school. Drawing on data from an ongoing study, the social and academic profile of new undergraduated students in the field of education is explored. This paper reports details of four groups of students entering the School of Education at Córdoba University arranged in terms of their previous educational experience. The results are shown by grouping the new students on the basis of prior formal education experiences, and they suggest an important participation of non traditional students and high diversity in different dimensions.